Time‐Varying Clearance and Impact of Disease State on the Pharmacokinetics of Avelumab in Merkel Cell Carcinoma and Urothelial Carcinoma. (25th April 2019) - Wilkins, Justin J.; Brockhaus, Brigitte; Dai, Haiqing; Vugmeyster, Yulia; White, Joleen T.; Brar, Satjit; Bello, Carlo L.; Neuteboom, Berend; Wade, Janet R.; Girard, Pascal; Khandelwal, Akash
Abstract : Avelumab, a human anti–programmed death ligand 1 immunoglobulin G1 antibody, has shown efficacy and manageable safety in multiple tumors. A two‐compartment population pharmacokinetic model for avelumab incorporating intrinsic and extrinsic covariates and time‐varying clearance (CL) was identified based on data from 1, 827 patients across three clinical studies. Of 14 tumor types, a decrease in CL over time was more notable in metastatic Merkel cell carcinoma and squamous cell carcinoma of the head and neck, which had maximum decreases of 32.1% and 24.7%, respectively. The magnitude of reduction in CL was higher in responders than in nonresponders. Significant covariate effects of baseline weight, baseline albumin, and sex were identified on both CL and central distribution volume. Significant covariate effects of black/African American race, C‐reactive protein, and immunogenicity were found on CL. None of the covariate or time‐dependent effects were clinically important or warranted dose adjustment.